2011
DOI: 10.1053/j.gastro.2011.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-12 Converts Foxp3+ Regulatory T Cells to Interferon–γ-Producing Foxp3+ T Cells That Inhibit Colitis

Abstract: Regulatory T (Treg) cells are plastic, but the in vivo mechanisms by which they are converted into Foxp3+interferon (IFN)-γ+ T cells, and whether these converted cells retain the ability to inhibit colitis, are not clear. Methods Foxp3+ Treg cells were generated by culture of naïve CD4+ T cells from Foxp3GFP CBir1 T-cell receptor (TCR) transgenic (CBir1-Tg) mice, which are specific for CBir1 flagellin (an immunodominant microbiota antigen), with transforming growth factor (TGF)-β. Foxp3GFP+ CBir1-Tg Treg cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
127
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 31 publications
11
127
2
Order By: Relevance
“…This question is of the utmost importance both for fundamental immunology and for clinical practice. Indeed, the original experiments of Medawar showed that the brain is an immunologically privileged site for skin allografts (45, Indeed, others have shown that OX40, CTLA-4, and CpG could all alter the suppressive properties and, in some cases, the phenotype of Tregs (8,27,(36)(37)(38)(39)(40)(41)(42)(43)(44). However, we ruled out this hypothesis by tracking the Tregs in vivo: the addition of CpG to immunomodulatory antibody therapy resulted in the depletion of i.t.…”
Section: Discussionmentioning
confidence: 91%
“…This question is of the utmost importance both for fundamental immunology and for clinical practice. Indeed, the original experiments of Medawar showed that the brain is an immunologically privileged site for skin allografts (45, Indeed, others have shown that OX40, CTLA-4, and CpG could all alter the suppressive properties and, in some cases, the phenotype of Tregs (8,27,(36)(37)(38)(39)(40)(41)(42)(43)(44). However, we ruled out this hypothesis by tracking the Tregs in vivo: the addition of CpG to immunomodulatory antibody therapy resulted in the depletion of i.t.…”
Section: Discussionmentioning
confidence: 91%
“…Th1-type Tregs expressing high levels of TBX21, IFNγ, and the surface marker CXCR3 have been identified in numerous disease settings, including colitis, infection, and autoimmune disease (13,(45)(46)(47). Tregs isolated ex vivo from patients with MS and T1D secrete more IFNγ and possess a functionally impaired phenotype; they do not suppress as effectively as Tregs isolated from healthy individuals (13,14).…”
Section: Cd44mentioning
confidence: 99%
“…The cytokine-producing Treg in these studies were anergic in vitro without the addition of IL-2, and were suppressive in Tconv co-cultures ( Refs 54,68,70,71,72 A beneficial role in the protection against infection has been proposed for cytokineproducing Treg (Refs 54, 73, 76), with some evidence for specific expansion and cytokine production against certain pathogenic antigens (Refs 54, 76). Moreover, there is evidence that such Treg may play a beneficial role during transplantation (Refs 76, 78): if IFN-γ production is blocked or specifically knocked out in Treg in a transplant model, mice suffer from graftversus-host disease.…”
Section: Introductionmentioning
confidence: 97%